1999
DOI: 10.1046/j.1525-1373.1999.d01-54.x
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Clinical Measles Virus Strains in Hispid Cotton Rats

Abstract: An alternative model to nonhuman primates to study measles virus (MV) pathogenesis, to evaluate potential MV vaccines, or to screen for potential antivirals effective against this virus is highly desirable. The laboratory-adapted Edmonston strain of MV has been reported to replicate in the lungs of hispid cotton rats following intranasal inoculation, immunosuppress infected animals, and disseminate widely from the lungs, making these animals a candidate model. However, clinical MV strains have generally not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The previous data indicated that the measles virus also uses two receptors in cotton rats that are presumably homologous to the human molecules [15]. Previous studies have documented that cotton rats are susceptible to infection by both vaccine and wild-type measles virus without adaptation [12,13]. However, in regards to in vitro infection of CRL cells, the results of this study revealed that wtMeV does not grow efficiently under primary infection, obtaining the ability to adapt after one or more passages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous data indicated that the measles virus also uses two receptors in cotton rats that are presumably homologous to the human molecules [15]. Previous studies have documented that cotton rats are susceptible to infection by both vaccine and wild-type measles virus without adaptation [12,13]. However, in regards to in vitro infection of CRL cells, the results of this study revealed that wtMeV does not grow efficiently under primary infection, obtaining the ability to adapt after one or more passages.…”
Section: Resultsmentioning
confidence: 99%
“…Cotton rats (Sigmodon hispidus) are unique rodents because of their susceptibility to human pathogens [9][10][11]. Since 1992, the cotton rat has been used in MeV research and previous studies have documented its susceptibility to infection with both vaccine and wtMeV [12,13]. The susceptibility of cotton rat to MeV infection via intranasal inoculation is of value to the investigation of measles pathogenesis and vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Although many species of cotton rats have been classified in the wild, only two have been inbred and are currently used for biomedical research, S. hispidus and S. fulviventer . Over the years, S. hispidus has been shown to support replication of a broad spectrum of human respiratory viruses including respiratory syncytial virus (RSV) [1], measles virus [2,3], several adenovirus serotypes [4,5], para-influenza virus type 3 [6], and human metapneumo virus [7-9]. Fewer studies have been performed using S. fulviventer , although there is some suggestion that they are differences in permissiveness and pathogenesis to certain pathogens when compared to S. hispidus [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…The cotton rat ( Sigmodon hispidus ) has proven to be a semipermissive (titer of inoculum correlates with titer of output virus) small animal model for the study of MV pathogenesis. MV replicates in lung tissue, mediastinal lymph nodes and spleen and viral RNA can be found in peripheral blood lymphocytes [15] , [16] , [17] , [18] . In addition, there are differences in viral spread and the immune suppressive capacity between wild type and vaccine strains.…”
Section: Introductionmentioning
confidence: 99%